CRAN-21. PHASE II STUDY OF PEGINTERFERON ALFA-2b (PEGINTRON)/SYLATRON FOR PEDIATRIC PATIENTS WITH PROGRESSIVE OR RECURRENT CRANIOPHARYNGIOMA FOLLOWING RADIOTHERAPY: A PEDIATRIC BRAIN TUMOR CONSORTIUM STUDY (PBTC-039). Issue 2 (22nd June 2018) - Goldman, Stewart; Pollack, Ian; Kun, Larry; Billups, Catherine; Broniscer, Alberto; Robinson, Giles; Dhall, Girish; Robison, Nathan; Panigrahy, Ashok; Poussaint, Tina Young; Adesina, Adekunle; Onar-Thomas, Arzu; et al.
Abstract: Despite complete resection, 20% -50% of pediatric craniopharyngiomas experience recurrence. Subtotal resection followed by radiation achieves comparable results. More effective therapies are needed. In tumor cell lines, prolonged exposure to interferon optimizes the anti-proliferative and anti-angiogenic effect. Conjugating proteins with poly-ethylene-glycol (PEG) lengthens the plasma half-life by reducing sensitivity to proteolysis, providing protracted activity. Stratum II of the PBTC-039 study proposed to estimate the sustained objective response rate (ORR=CR + PR) associated with PEGIntron/Sylatron in progressive/recurrent craniopharyngiomas post RT. Simon's 2-stage design with 10% unacceptable and 35% desirable ORR required a total sample size of 19 (α=β=0.1). An interim analysis was planned after 11 patients and ≥2 objective responses within the first year were needed to expand accrual. 12 patients were enrolled 11, (5 males and 6 females) were eligible and evaluable. Median age at diagnosis was 7.0 years (range, 2.0–12.4) and at study entry was 20.5 years (6.1–25). Median number of cycles received was 6 (1–17). No grade 4 adverse events (AE) were reported. Grade 3 attributable AEs included decreased neutrophil count, nausea, fatigue, fever, headache and anorexia (n=1 each). No objective responses were observed. With a median follow-up 12.9 months (3.2 - 25.7), 5/11 patients have progressed at a median of 8.2 months (2.9–19.5). Other off-treatment reasons were AE, alternative therapy/withdrawal and not meeting weight criteria. PFS estimate at 1-year was 68.2% ± 14.5%. One patient remains on treatment. Although well tolerated, stratum II was permanently closed after interim analysis due to lack of objective responses.